Dampak karakteristik tim audit, independensi, kompetensi dan fee audit terhadap kualitas audit: Dampak mediasi proses audit efektif - Subiyantoro Subiyantoro (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study investigates the direct and mediated effects of audit team characteristics, independence, competence, and audit fees on audit quality within Public Accounting Firms (KAP) in DKI Jakarta. Using a survey method and Partial Least Squares (PLS) analysis, the research reveals that auditor independence has a significant direct positive impact on audit quality. At the same time, team characteristics, competence, and fees show no direct influence. However, auditor competence indirectly enhances audit quality when mediated by an effective audit process. The audit process does not mediate the effects of team characteristics, independence, or fees. These findings underscore that upholding auditor independence and strengthening competence—supported by robust audit procedures—are essential to improving audit quality, offering practical insights for firms and regulators in enhancing oversight and professional standards.. Public Interest Statement This study has a public interest in improving the accountability and transparency of audit results conducted by Public Accounting Firms (KAP), especially in the DKI Jakarta area. By empirically testing how audit team characteristics, independence, competence, and audit fees affect audit quality and the mediating role of the audit process, this study contributes to strengthening the public financial oversight system and protecting the interests of stakeholders, including investors, regulators, and the general public. The results of the study are expected to be the basis for improving audit policies and practices in Indonesia.